The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/978-1-4614-3461-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Antibodies Directed Against Carbohydrate Tumor Antigens

Abstract: Healthy persons carry within their pool of circulating antibodies immunoglobulins preferentially of IgM isotype, which are directed against a variety of tumor-associated antigens. In closer scrutiny of their nature, some of these antibodies could be defined as naturally occurring antibodies due to the germline configuration of the variable immunoglobulin region. The majority of these immunoglobulins recognize carbohydrate antigens which can be classified as oncofetal antigens. Many of these IgM antibodies pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 87 publications
2
18
0
1
Order By: Relevance
“…It has previously been shown that TACA-specific Abs can exert antitumor effect through mechanisms such as direct tumoricidal effect (apoptosis induction), or Ab-dependent cell-mediated cytolysis (ADCC), or activation of the complement system (CDC) (14). In our ADCC assays, hPus-Abs effectively assisted the lysis of the (1→6)-b-glucan glycotope-positive U937 cells by NK cells freshly prepared from human PBMCs (Fig.…”
Section: (1→6)-b-glucan-specific Abs Exhibit Tumoricidal Activities Imentioning
confidence: 62%
See 3 more Smart Citations
“…It has previously been shown that TACA-specific Abs can exert antitumor effect through mechanisms such as direct tumoricidal effect (apoptosis induction), or Ab-dependent cell-mediated cytolysis (ADCC), or activation of the complement system (CDC) (14). In our ADCC assays, hPus-Abs effectively assisted the lysis of the (1→6)-b-glucan glycotope-positive U937 cells by NK cells freshly prepared from human PBMCs (Fig.…”
Section: (1→6)-b-glucan-specific Abs Exhibit Tumoricidal Activities Imentioning
confidence: 62%
“…Subsequent studies have confirmed that the modification of cellular glycosylation is indeed a common phenotypic change of cancer cells that mainly affects the outer part of glycans (9)(10)(11)(12)(13)(14). Today, abnormal glycosylation is recognized as one of the hallmarks of cancer cells, and a number of tumor-associated carbohydrate Ags (TACAs) have been identified, which include: 1) H/Le(y)/Le(a) in primary non-small cell lung carcinoma; 2) sialyl-Le(x) (SLe(x)) and sialyl-Le(a) (SLe(a)) in various types of cancer; 3) Tn and sialyl-Tn in colorectal, lung, and many other cancers; 4) GM2, GD2, and GD3 gangliosides in melanoma and neuroblastoma; and 5) globo-H in breast, ovarian, and prostate cancer (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). TACAs may contribute to tumorigenesis and are capable of inducing antitumor adaptive immune responses in cancer patients (8-10, 14, 15).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Apoptotic destruction induced by CD176 antibody of the natural antibody repertoire may provide an explanation for this phenomenon (13). Tumor-specific apoptosis mediated by natural carbohydrate-reactive IgM antibodies in humans has been observed and may lead to new strategies for anticancer immunotherapy (24). Additionally, CD176 antibody treatment can prevent tumor metastasis (18).…”
Section: Cd176mentioning
confidence: 99%